Management of Ginger Bacterial Wilt (Ralstonia solanacearum) Epidemics through Soil Solarization and Botanical Mulch at Tepi, Southwestern Ethiopia - Merga Jibat Guji; Abukiya Getu Baliher (Agro Bali : Agricultural Journal, 2022)
Ginger is a valuable revenue crop for Ethiopian farmers in many sections of the country. In Ethiopia, bacterial wilt disease is a serious constraint to ginger output. Heavy losses are common as a result of the disease, with extra losses happening as a result of the disease's boundaries, which prevent continued production in infested areas. To investigate the impact of soil solarization and botanical mulch on epidemics of bacterial wilt of ginger in Tepi, Southwestern Ethiopia, field studies were done throughout the 2019 and 2020 main cropping seasons. Four different soil solarization periods were used: two weeks, four weeks, six weeks, and eight weeks before planting, with four different botanical mulches: vetivar grass, lemon grass, Chinese chive, and lantana camara added after planting. The control plots were not solarized nor mulched. Treatments were placed in factorial arrangements with three replications using a randomized full block design. In comparison to the control, soil solarization combined with lemon grass mulch treatment dramatically reduced bacterial wilt mean severity by 22.1 percent to 42.2 percent. These treatments also significantly lowered the rate of AUDPC and disease progression. When compared to control, soil solarization for eight weeks combined with lemon grass mulch resulted in the lowest disease severity (42.2%) and AUDPC (33.8%). Overall, the findings of this study showed that using a mixture of soil solarization and botanical mulches to slow down bacterial wilt outbreaks and recover ginger production and productivity, along with other crop management strategies, was effective.